The Role of The Election Supervisory Body (BAWASLU) In Handling Violations of the 2024 Regent and Deputy Regent Elections in South Tapanuli, Indonesia - Damanik, Dwi Rodearni; Siregar, Hisar (Manunggal Halim Jaya, 2025)
Regional Head Election (Pilkada) is a people's democratic party in electing regional heads and their deputies who come from proposals from certain political parties, combinations of political parties or independently and who have met the requirements. The general election process for regional heads is regulated in a new law, namely Law Number 10 of 2016 concerning the Election of Regional Heads, Bawaslu Regulation Number 8 of 2020 concerning Handling Violations in the Election of Governors and Deputy Governors, Regent and Deputy Regent, and Mayor and Deputy Mayor. and Joint Regulation No. 5 of 2020 concerning Integrated Law Enforcement Centers in the Election of Governors and Deputy Governors, Regent and Deputy Regent, and Mayor and Deputy Mayor. Regency/City Bawaslu has the authority to receive and follow up on reports relating to alleged violations of the implementation of laws and regulations governing elections, whether violations of the code of ethics, administration or criminal acts. The research results show that 1) handling violations of the code of ethics carried out by the election organizer, namely the KPU. 2) handling election administration violations related to accepting registration for individual candidates in the 2024 Pilkada. 3) handling election criminal violations based on reports related to criminal acts of forging signatures as a requirement for candidate administration and determining candidate pairs in the 2024 Regent and Deputy Regent elections.